Spacecraft sun-pointing using coplanar solar panels data and magnetic field measurements - Mohammad Abdelrahman, Mohammad Ibraheem (2013)
The orientation of the solar panels towards the sun is one of the major tasks for the ADCS. After separation from the launcher the sun-acquisition mode takes place. Following to the sun-acquisition mode the ADCS switches to the sun-pointing mode. Both modes can be handled either by an active actuation and measurements using sun sensors, or passively, by investigating the sun angle w.r.t the spacecraft orbit and adjust the setting angles of the solar panels, area exposed to the sun and spacecraft inertia such that during earth- pointing mode the solar panels can capture the required energy to fulfil the spacecraft power profile. The drawbacks of the passive approach are the requirement of relatively wide-area solar panels, complexity of the structure and the degradation of the solar power provided by the solar panels due to the degradation of the orbit and uncompensated change of the sun angle w.r.t the spacecraft orbit. The goal of this paper is to develop an algorithm for sun vector estimation without any explicit measurements from sun sensors. The developed algorithm is applied to a spacecraft designed as a passively sun-pointed spacecraft with coplanar solar panels. The design of the estimator follows the Extended Kalman Filtering EKF scheme. The proposed estimator consists of two uncoupled sub-estimators. One sub-estimator dedicated for attitude and rate estimation, where the process dynamics are derived through the augmentation of the spacecraft nonlinear dynamics and quaternion kinematics. Then, the magnetometer measurements and their corresponding time derivatives are used to represent the measurement model. The other sub-estimator is derived for the estimation of the Sun vector based on solar panels measurements in terms of output current. Another estimator also has been introduced by combining the two uncoupled sub-estimators into one estimator for attitude, rate, and sun vector estimation. The controller for the sun-pointing mode is based on Modified State-Dependent Riccati Equation MSDRE, developed previously by the author to solve a trajectory tracking/model following problem. EgyptSat-1, is a remote sensing satellite in a near circular sun-synchronous orbit. The flight scenario of EgyptSat-1 does not include a sun-pointing mode; it utilizes four coplanar solar panels to provide the satellite with the required power. The proposed algorithm has been applied to EgyptSat-1. The satellite is switched from earth-pointing to sun-pointing mode using the estimated sun-vector. The algorithm successfully has been applied to the spacecraft for tracking the sun vector with pointing accuracy within 5 degrees without any change in the hardware sizing. The combined estimator shows relatively better enhancement and fast convergence in attitude and Sun vector estimation however, real time implementation and computing efforts should be investigated. For the same power budget, the improvement in sun-pointing is interpreted as a reduction of the solar panels area and hence the overall mass budget.